El agroturismo como una alternativa de desarrollo sostenible en la parroquia de San Luis, provincia de Chimborazo - Auquilla Yuquilema, Blanca Alexandra (2025)
The Agrotourism is an activity that provides several benefits for developing communities. Tourism allows for the marketing of different foods, food services, and accommodations, as well as the trading of other goods. Regarding the importance of Agrotourism, the current research aims to determine the relationship between Agrotourism and sustainable development of the San Luis parish in Chimborazo Province-Ecuador. The methodology applied was correlational. The research design was cross-sectional and non-experimental. Qualitative methods, such as observation, and quantitative methods, such as the survey and the classification test, were appropriate for data collection. The researcher developed and validated two questionnaires to obtain information on Agrotourism and sustainable development. The results suggest a good relationship between the study variables by obtaining a significance value of less than 0.05. Regarding the community and experience dimensions, a positive relationship was found with sustainable development, while the agricultural products dimension had a negative relationship. The main conclusion derived from this study is that training the population in Agrotourism is essential to ensure good long-term development, helping at the same time to preserve all the natural resources of the parish.